14- to 16-Month-Olds Attend to Distinct Labels in an Inductive Reasoning Task - Switzer, Jessica L.; Graham, Susan A. (Frontiers in Psychology, 2017)
We examined how naming objects with unique labels influenced infants’ reasoning about the nonobvious properties of novel objects. Seventy 14- to 16-month-olds participated in an imitation-based inductive inference task during which they were presented with target objects possessing a non-obvious sound property, followed by test objects that varied in shape similarity in comparison to the target. Infants were assigned to one of two groups: a No Label group in which objects were introduced with a general attentional phrase (i.e., “Look at this one”) and a Distinct Label group in which target and test objects were labeled with two distinct count nouns (i.e., fep vs. wug). Infants in the Distinct Label group performed significantly fewer target actions on the high-similarity objects than infants in the No Label group but did not differ in performance of actions on the low similarity object. Within the Distinct Label group, performance on the inductive inference task was related to age, but not to working memory, inhibitory control, or vocabulary. Within the No Label condition, performance on the inductive inference task was related to a measure of inhibitory control. Our findings suggest that between 14- to 16-months, infants begin to use labels to carve out distinct categories, even when objects are highly perceptually similar.